IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI MATEMATIS SISWA SMP NEGERI 30 MEDAN - Sinabang, Esra; Simanjuntak, Sinta Dameria; Imelda, Imelda (Unika Santo Thomas Medan, 2023)
This study aims to determine whether the implementation of problem-based learning models can improve students' mathematical numeracy literacy skills in class VIII SMP Negeri 30 Medan. This research method uses Classroom Action Research (CAR). The research procedure is in the form of a cycle. Each cycle consists of 4 stages, namely: planning, implementation of action, observation and reflection. Data collection techniques through observation and tests. This data collection uses several instruments in the form of teacher observation sheets, student observation sheets. Meanwhile, to determine the ability of students' mathematical numeracy literacy tests were used. The results showed that the use of problem-based learning models can improve students' mathematical numeracy literacy skills in the mathematics subject matter of cubes and blocks. From the average initial ability score of 50, the average value of students' mathematical numeracy literacy ability in cycle I is 64 and the average value of students' mathematical numeracy literacy ability in cycle II is 78 and the average value of teacher and student activities in cycle I is 63% and 55%, and cycle II, namely 83% and 82%.